Keadilan Dalam Syariat Islam Pembagian Waris Terhadap Anak Angkat - Emy Handayan; Mas’ut; Agus Sarono (Wijayakusuma Law Review, 2025)
Inheritance law is very important, this is proven by the results of research by students of the Faculty of Law, Jayabaya University, Jakarta in order to fulfill the requirements for taking the Islamic Law II exam in the 1978/1980 academic year period. It appears in the statistics of cases entered and determined by the Religious Court in the Special Capital Region of Jakarta Raya, inheritance problems are ranked 2nd after marriage problems (Marriage, Divorce, and Reconciliation). The form and system of inheritance law are very closely related to the form of society in a region or place. If it can be said that law is one aspect of culture, both spiritual and physical, this is perhaps one of the reasons why there are various legal systems, especially inheritance law. Law determines the form of society, a society that is not yet known can be tried to understand it in its basics by studying the laws that apply in society. In Indonesia, there are three legal systems that regulate the application of issues and problems regarding adoption. The three legal systems are Islamic law, customary law, and Western law. However, the author will not discuss the customary law system and the Western law system, because he will focus on Islamic inheritance law. Based on the explanation above, it can also be concluded that the principle of proportional justice means giving a portion to someone based on their services or contributions. Thus, everyone does not have to get the same portion if the efforts made are different. Adopted children in the view of the principle of proportional justice can be given a more sufficient portion, as per article 209 of the KHI. This provision is of course followed by the condition that the child has contributed to their adoptive parents. The use of justice as a legal framework will make the law flexible and create happiness for humans.